Crianças infames: fragmentos de vidas no arquivo público e histórico de Ribeirão Preto - Ferreira, Emerson Benedito (2014)
This thesis is the result of a survey conducted in two cases and two Criminal Investigation Police discovered the Public Archives and History of Ribeirao Preto. In them we find four poor children who were raped at the turn of the nineteenth and early twentieth centuries. With the theoretical framework and methodology supported in Michel Foucault, the main trunk of the research is focused on the rescue of those children stories from the perspective of their own accounts. It is also the object of this work to investigate, through the intersection of the four procedural documents, the particularities of each of the crimes, unraveling how abused those children faced intensifying legal actions in their lives, and how the devices of sexuality and alliance, which had as a principle meet the medical/legal policy that historical period, seeking to punish deviant behavior, across each of those bodies. The study also found that the way assimilated elite and used the legal instrument to build their worldviews. We conclude with the work the new world designed in the late eighteenth century was built by and for the ruling elite. The speeches, laws and standards in Lawsuits recorded camouflage schemes standardization of social life, which led to all, in defiance of the law were to apply the few ( the only undesirable ). As one of the conclusions of the study it appears that the trials worked, actually, as an educational showcase the deviant, sanctioning their actions and berating his excesses. The shock of these infamous power with children was the only way to get out of the dark stories. Without this meeting, we would never know of their existence.